Inventeringsdata för fåglar, mossor, lavar och kärlväxter från 40 tall- och granbestånd i Sydsverige - Petersson, Lisa; Lariviere, Delphine; Holmström, Emma; Lindbladh, Matts; Felton, Adam (Swedish National Data Service, 2023)
The aim of the data collection was to examine differences in biodiversity between two different age classes of production forest stands. Surveys were conducted between 2016-2017 in forty managed production forest stands in southern Sweden. Stands are dominated by two different tree species: Scots pine and Norway spruce and belong to two different age classes: 55 (+/- 5) and 80 (+/- 5) year old. In total ten stands of each category (tree species and age class) were surveyed. There are four separate data sets for species: birds, bryophytes, epiphytic lichens and vascular plants. Species data consists of presence/absence data for the different stands. There is also one data set with stand structures. The five different data sets can be connected using a stand ID that can be found in all of the files. Data consists of information about 26 bird species, 84 bryophyte species, 57 lichen species and 102 vascular plant species. Files consist of 5 separate matrices with 40 rows that are stored in .csv format (comma delimited). Data set 'bird.csv' has 40 rows and 29 columns. Data set 'bryophyte.csv' has 40 rows and 87 columns. Data set 'epilichen.csv' has 40 rows and 60 columns. Data set 'vascularpl.csv' has 40 rows and 105 columns. Data set 'stand_structures.csv' has 40 rows and 7 columns. All data sets have a column "stand", which consist of stand IDs which can be used to connect the different data sets with each other. Information about tree species and stand age class is also provided in the data. For bird species common English names are used. Scientific names are used for vascular plants (Dyntaxa 2019), bryophytes (Hallingbäck 2006) och lichens (Santesson's Checklist of Fennoscandian Lichen-forming and Lichenicolous Fungi 2020). Data was collected during summer of 2016 (birds, bryophytes, vascular plants and forest structure data) and during summer of 2017 (lichen data and forest structure data). Data consist of information from fourty stands. In each stand, 10 plots of 100m2 were used for inventoring bryophytes and ...